THE USE OF INFORMAL DIGITAL LEARNING OF ENGLISH (IDLE) AMONG PREPARATORY SCHOOL STUDENTS - Ertan Altınsoy (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This mixed-methods study investigates the role of Informal Digital Learning of English (IDLE) among 82 English preparatory school students (aged 17–20) in Turkey, focusing on the frequency of form- and meaning-focused activities, preferred digital platforms, gender differences, and the perceived impact on language skills. Data were collected using a 14-item bilingual FMIDLES scale, enhanced with open ended questions to validate the findings. Descriptive statistics revealed that meaning-focused activities—such as watching English videos, social media engagement, and online reading—were more frequent than form-focused activities, with significant gender-based variation. Pearson correlation analysis showed strong, statistically significant relationships between meaning-focused IDLE and perceived improvements in listening. Form-focused IDLE correlated significantly only with perceived writing improvement. The study highlights the pedagogical value of integrating informal digital tools—including AI-based writing assistants—into formal instruction, while considering gender-based learning preferences to maximize learner engagement and language.